1982
DOI: 10.1007/bf00011966
|View full text |Cite
|
Sign up to set email alerts
|

The nature of fish communities: A factor influencing the fishery potential and yields of tropical lakes and reservoirs

Abstract: The discrepancy between high primary production and poor fish yields in some tropical reservoirs, especially in Souht East Asia, is apparently due to the fact that not all available trophic levels are utilized . Data analysis has shown that this is due to the riverline origin of fish communities which are not well adapted to lacustrine habitats in such lakes and reservoirs . These fishes are able to inhabit only a relatively narrow belt of the shallow inshore area . It has been shown that fish are rare in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…With the exception of East Africa the tropics have few natural lakes with lacustrine fish species (Fernando & Holèik, 1982) and the fish fauna of Amazonian reservoirs is mainly of riverine origin. In Brokopondo Reservoir, much like other Neotropical reservoirs (Araujo-Lima et al, 1995;Agostinho et al, 1999), the fish community of shore habitat had more species, higher species diversity and higher evenness than the open water community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of East Africa the tropics have few natural lakes with lacustrine fish species (Fernando & Holèik, 1982) and the fish fauna of Amazonian reservoirs is mainly of riverine origin. In Brokopondo Reservoir, much like other Neotropical reservoirs (Araujo-Lima et al, 1995;Agostinho et al, 1999), the fish community of shore habitat had more species, higher species diversity and higher evenness than the open water community.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by (1) the greater structural complexity of shore habitat (woody debris, dead bushes, submerged macrophytes) compared to open water habitat and (2) the fact that most riverine fishes have experienced littoral-like conditions in their pre-impoundment habitat (e.g. floodplains) and thus tend to stay near the shore when colonizing reservoirs whereas only few species are preadapted to exploit the open water habitat (Fernando & Holèik, 1982). Cichlids, which are known to thrive in tropical lakes and reservoirs (Fernando & Holèik, 1982), were also dominant in the littoral of Brokopondo Reservoir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the occurrence of environmental impacts is inherent with any impoundment, a process fundamentally linked to the control of river flow. Though describing a single hydrological attribute, water flow represents the main force behind freshwater ecosystems, and it is responsible for their geological/hydrological structure, productive dynamics (matter and energy), nutrient cycling and the distribution and evolution of the biota (Poff et al, 1997). As a consequence, the loss of natural flow regimes has far-reaching impacts, including alterations in pristine hydrological dynamics, historical patterns of biological production, distribution of biodiversity in space and time, and changes in functions and services provided by aquatic ecosystems (Nilsson et al, 2005).…”
Section: Impacts Caused By Damsmentioning
confidence: 99%
“…The absence of pelagic species in fluvial systems has been considered a determining factor of low species richness and abundance observed in open areas of reservoirs in South America. Thus, fish species in neotropical reservoirs are concentrated mainly in littoral areas and near the mouth of tributaries (Agostinho et al, 1999 andFernando andHolcík, 1982;Gomes and Miranda, 2001). This study showed that, among others factors, water dynamics in reservoirs had a major role selecting which fish species will occupy these environments, imposed basically by ecomorphological constraints.…”
Section: Discussionmentioning
confidence: 99%